Remission of Inflammatory Bowel Disease in Glucose-6-Phosphatase 3 Deficiency by Allogeneic Haematopoietic Stem Cell Transplantation. (3rd June 2019) - Bolton, Chrissy; Burch, Nicola; Morgan, James; Harrison, Beth; Pandey, Sumeet; Pagnamenta, Alistair T; ,; Taylor, Jenny C; Taylor, John M; Marsh, Judith C W; Potter, Victoria; Travis, Simon; et al.
Abstract: Mendelian disorders in glucose-6-phosphate metabolism can present with inflammatory bowel disease [IBD]. Using whole genome sequencing we identified a homozygous variant in the glucose-6-phosphatase G6PC3 gene [c.911dupC; p.Q305fs*82] in an adult patient with congenital neutropenia, lymphopenia and childhood-onset, therapy-refractory Crohn's disease. Because G6PC3 is expressed in several haematopoietic and non-haematopoietic cells it was unclear whether allogeneic stem cell transplantation [HSCT] would benefit this patient with intestinal inflammation. We show that HSCT resolves G6PC3- associated immunodeficiency and the Crohn's disease phenotype. It illustrates how even in adulthood, next-generation sequencing can have a significant impact on clinical practice and healthcare utilization in patients with immunodeficiency and monogenic IBD.